School Readiness of Prospective Cimanggis Character Elementary School Students Before and After the Covid-19 Pandemic - Riski Septiadevana; Edianna Putri Mayangsari; Trias Syaifulina; Yulia Pratiwi (Universitas Nusantara PGRI Kediri, 2026)
A child’s readiness to be ready for elementary school is the most important thing in the education system. During this period, a child undergoes a transition in both their learning and social environments. School readiness tests aim to assess a child’s current abilities and developmental maturity. This helps parents and school officials understand various aspects of a child’s development, such as basic abilities, skills, and maturity. However, during the pandemic, most students engaged in remote learning from home. Certain aspects of a child’s development were not optimally stimulated because the learning process occurred remotely without face-to-face interaction. This article aims to provide an analysis of the school readiness of prospective students at Cimanggis Karakter Elementary School before and after the pandemic. The research method used is descriptive quantitative, employing a t-test on the School Readiness Test results of prospective students at Cimanggis Karakter Elementary School from 2019 and 2021. The results of the study indicate that the School Readiness Test scores of students prior to the pandemic demonstrated a higher level of readiness compared to those after the pandemic. Students who took the test after the pandemic were kindergarten B students who were unable to participate in face-to-face learning because instructional activities were conducted online.